Ergonomic factors affecting comprehension levels of traffic signs: A critical review - Shyrle Berrio; Lope H. Barrero; Laura Zambrano; Eleonora Papadimitriou (International Journal of Transportation Science and Technology, 2023)
Comprehension of traffic signs is important to road safety. This review aims to study the extent to which road users in different countries comprehend traffic signs and to identify which ergonomic principles in traffic sign design can affect the levels of comprehension. We conducted an extensive literature review dealing with comprehension of public traffic signs directed at any road user. We searched Journal articles indexed by Scopus, ScienceDirect, and Web of Science. The search identified 35 articles that assessed the comprehension of 931 traffic signs in 26 countries, including six studies that tested the comprehension of new versus existing traffic signs. Various methods have been implemented to measure traffic signs’ comprehension levels and assess traffic sign design’s conformity to different ergonomic principles. Results indicate high variability in the comprehension levels of signs, e.g., signs such as “Road works” and “No U-turn” are highly comprehended (comprehension levels over 90 %), while other signs like “termination of road” are rarely comprehended by road users. Regarding the acceptable comprehension levels, 23.1 % of the assessed traffic signs achieved levels above 85 %; and 53.3 % of signs have comprehension levels lower than 67 %. On the other hand, twenty-four studies evaluated how traffic signs comply with ergonomic design principles. Incorporating ergonomic principles into the design of traffic signs can improve comprehension levels. However, apart from the familiarity, there is uncertainty about the ergonomic principles that could maximize the comprehension of traffic signs. Efforts should be made to ensure that different populations of road users sufficiently comprehend traffic signs.